2020
DOI: 10.20944/preprints202004.0439.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly Conserved Homotrimer Cavity Formed by the SARS-CoV-2 Spike Glycoprotein: A Novel Binding Site

Abstract: An important stage in SARS-CoV-2 life cycle is the fusion of spike(S) protein with the ACE2 host-cell receptor. Therefore, to explore conserved features in S protein dynamics and to identify potentially novel regions for drugging, we measured variability derived from 791 viral genomes and studied its properties by MD simulation. The findings indicated that S2 subunit (HR1, CH, and CD domains) showed low variability, low fluctuations in MD, and displayed a trimer cavity. By contrast, the RBD domain, which is ty… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 83 publications
2
33
0
Order By: Relevance
“…The virus spike's transmembrane-glycoprotein,a homotrimer [9] is responsible for the entry of viral RNA into the host cell. Its S1 subunit attaches to ACE2 receptors of the host cell which stimulates formation of TMPRSS2 (Transmembrane protease Serin-2) [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The virus spike's transmembrane-glycoprotein,a homotrimer [9] is responsible for the entry of viral RNA into the host cell. Its S1 subunit attaches to ACE2 receptors of the host cell which stimulates formation of TMPRSS2 (Transmembrane protease Serin-2) [10] .…”
Section: Introductionmentioning
confidence: 99%
“…1 ) [ 3 ]. The S1 subunit with the larger receptor binding domain and the S2 subunit which induces the membrane fusion polypeptides forming the six helix bundle which results in complete fusion and insertion of viral genome to the host cell cytosol [ 6 ]. Hence, structural analysis on the S-protein could reveal possible mechanisms by which the viral replication could be terminated/controlled [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rapidly emerging plethora of computational studies examined SARS-CoV-2-RBD interactions with ACE2 enzyme using the recent crystal structures [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. It was proposed that SARS-CoV-2-RBD may have adopted a specific strategy for achieving favorable binding affinity by exploiting the larger binding interface as compared to the SARS-CoV-RBD that employs the fewer contacts and could rely only on major hotpot centers [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated that the dynamics of glycan shield can be allosterically coupled to conformational changes, regulating the equilibrium transitions and response to the host receptor. MD simulations of the SARS-CoV-2 spike glycoprotein identified the changes in the molecular properties due to conformational flexibility [ 35 ]. Several computational methods were used to identify potential allosteric sites on the SARS-CoV-2 spike protein [ 36 ] and employed network modeling to suggest allosteric signaling as a possible mechanism underlying virus transmission in the SARS-CoV-2 spike proteins [ 37 ].…”
Section: Introductionmentioning
confidence: 99%